Jaga Diri di Baltik - Edmondus Iswenyo Noang (Global Political Studies Journal, 2022)
Finland is geographically and politically bordered by Russia. This makes Finland as buffer zone between Russia and Europe. Politically, Finland is a member of the European Union, but not a member of NATO. This article focuses on the reasons why Finland cooperates with NATO in the Political Framework on Cyber defence which was signed on February 16, 2017. The research methodology used is qualitative with a literature study method. The problem analysis in this article uses complex interdependence theory. The article concludes that Finland and NATO need such cooperation as a precaution against future attacks such as the denial of service on websites of non-governmental organizations, companies, and the Ministry of Defense. For NATO, cooperation is a measure to anticipate threats that come from closest enemies who have the potential to steal information or secret documents of the organization.